Phenotypic modulation of auto-reactive cells by insertion of tolerogenic molecules via MSC-derived exosomes - Mokarizadeh, Aram (Vet Res Forum, 2012)
Auto-reactive cells-mediated immune responses are responsible for the current tissue damages during autoimmunity. Accordingly, functional modulation of auto-reactive cells has been a pivotal aim in many of recent studies. In the current study, we investigated the possibility for insertion of regulatory molecules onto auto-reactive cells through exosomal nano-shuttles as a novel approach for phenotype modification of auto-reactive cells. The exosomes were isolated from supernatant of mesenchymal stem cells culture. Resultant exosomes co-cultured with lymphocytes were harvested from established EAE mice in the presence of antigenic MOG(35-55 )peptide. After 24 hr, insertion of exosomal tolerogenic molecules (PD-L1, TGF-β, galectin-1) onto auto-reactive cells were explored through flow cytometry. The potency of exosomal inserted membrane molecules to modulate phenotype of auto-reactive lymphocytes was assessed upon ELISA test for their-derived cytokines IFN-γ and IL-17. Incorporation of exosomal molecules into lymohocytes’ membrane was confirmed by flow cytometric analyses for surface levels of mentioned molecules. Additionally, the decreased secretion of IFN-γ and IL-17 were detected in exosome pre-treated lymphocytes upon stimulation with MOG peptide. Mesenchymal stem cells -derived exosomes showed to be efficient organelles for insertion of bioactive tolerogenic molecules onto auto-reactive cells and modulation of their phenotypes.